2015
DOI: 10.1080/14786419.2015.1004174
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative determination of three pentacyclic triterpenes from fiveSwertiaL. species endemic to Western Ghats, India, using RP-HPLC analysis

Abstract: Aim of this study was to identify pentacyclic triterpenoids betulinic acid (BA), oleanolic acid (OA) and ursolic acid (UA) from five Swertia species endemic to Western Ghats, which are used as substitutes as well as adulterants to Swertia chirayita. Our results indicate that the concentration of active compound vary largely among and within the species from different localities. OA was found in a higher amount in all species compared to BA and UA. From the results, it was clear that BA, OA and UA are present i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…At present, quantification of the most important representatives of PCTs (betulin, erythrodiol, lupeol, betulinic acid, etc.) and their non‐volatile derivatives is carried out by high‐performance liquid chromatography (HPLC) with spectrophotometric, 13–21 mass spectrometry (HPLC–MS) 22,23 and tandem mass spectrometry (HPLC–MS/MS) 24–30 detection. The latter typically uses a multiple reaction monitoring (MRM) detection mode providing, in combination with atmospheric pressure chemical ionisation (APCI), an exceptional sensitivity and selectivity of PCTs analysis 29 .…”
Section: Introductionmentioning
confidence: 99%
“…At present, quantification of the most important representatives of PCTs (betulin, erythrodiol, lupeol, betulinic acid, etc.) and their non‐volatile derivatives is carried out by high‐performance liquid chromatography (HPLC) with spectrophotometric, 13–21 mass spectrometry (HPLC–MS) 22,23 and tandem mass spectrometry (HPLC–MS/MS) 24–30 detection. The latter typically uses a multiple reaction monitoring (MRM) detection mode providing, in combination with atmospheric pressure chemical ionisation (APCI), an exceptional sensitivity and selectivity of PCTs analysis 29 .…”
Section: Introductionmentioning
confidence: 99%
“…The medicinal value of Swertia chirata is due to the presence of some important bio-active compounds, such as secoiridoids, xanthonoids, triterpenoids etc. Among them, amarogentin and swertiamarin (Bhandari et al 2006;Gupta et al 2011;Samaddar et al 2013), mangiferin (Pandey et al 2012), oleanolic acid, and ursolic acid (Gao et al 2015 ;Kshirsagar et al 2015) are the most important bio-active compounds that have been considered as significant phytochemical markers and leading keys for the authentication of Swertia chirata.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, pentacyclic triterpenoids viz., UA, OA, and BA are industrially important plant-derived compounds, so efficient extraction is the first major step in the recovery, and refinement of these bio-active compounds. Extraction of these compounds was carried out using different conventional solid-liquid extraction techniques like soxhlet method (Gopal et al 2014), reflux method (Gao et al 2015, and cold extraction (Kshirsagar et al 2015). Moreover, quality of herbal medicines has been affected by various extraction parameters such as temperature, extraction time, type of solvent used, composition of different solvents, number of extraction steps, solid-to-liquid ratio, and mean particle size (Gad et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Reports for bioactive compounds quantification by chromatographic techniques are present [7,[23][24][25][26], however, to date no study has reported efficient extraction and validated UHPLC/PDA method for quantification of chiratol in raw herbal extracts. In continuation of research on biodiversity exploration for the human and plant health from biodiversity hotspot of the Himalayan region of India [27][28][29][30], we describe herein, characterization and prime extraction method along with the validated method for a selective protocol for the quantification of chiratol in the medicinal herbal extract of S. paniculata collected from high altitude region of the Uttarakhand (India).…”
Section: Introductionmentioning
confidence: 99%